Relation of Urokinase-Type Plasminogen Activator Expression to Presence and Severity of Atherosclerotic Lesions in Human Coronary Arteries - Kienast, Joachim; Padró, Teresa; Steins, Martin; Li, Chang-Xun; Schmid, Kurt W.; Hammel, Dieter; Scheld, Hans H.; van de Loo, Jürgen C. W. (Thrombosis and Haemostasis, 1998)
Urokinase-type plasminogen activator (UPA) has been implicated in a broad spectrum of pathological processes – e.g. cell adhesion, migration and proliferation and matrix remodeling – that are considered important features of atherogenesis and plaque disruption. In this study, we have analyzed the content and expression of UPA in human coronary arteries and its relation to the presence and severity of atherosclerotic lesions. Segments of coronary arteries obtained from human heart explants (n = 15) were classified by the presence and types of atherosclerotic lesions. UPA was quantitatively determined in protein extracts of the intimal and medial layers. In situ hybridization and immunohistochemical analyses were performed on serial sections of representative tissue specimens. UPA was detected in the extracts as pro-UPA, UPA complexed to plasminogen activator inhibitor-1, or as otherwise inactive UPA antigen, but not in the active two-chain form. Both functional and total UPA were increased several-fold in extracts of advanced lesions, while the ratios of functional over total UPA showed the opposite trend suggesting enhanced UPA inactivation and turnover. UPA expression in early atherosclerotic lesions was particularly prominent in areas of proliferating SMCs in the abluminal part of the neointima, whereas in advanced lesions UPA was widely expressed in macrophage-rich areas adjacent to the rims and shoulder regions of the necrotic cores. The results strongly suggest a causal involvement of UPA in coronary atherogenesis and its clinical outcome.